Association between Frozen Shoulder and Diabetes among Women of Reproductive Age (15–49 Years): A Systematic Review - Shahzaib Ud Din Hamza, Amsha Ishaq, Muhammad Sheraz Ali, Muhammad Babar, Tahira Farooq, Rabia Saeed Qureshi, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Diabetes mellitus (DM) has devastating effects on articulating joints, particularly the shoulder joint, which plays a critical role in mobility and functional activities. As a highly mobile synovial joint, the shoulder is more prone to degenerative changes, especially in individuals with DM. Purpose of Study: To evaluate the association between frozen shoulder (FS) and diabetes mellitus among diabetic women of reproductive age (15–49 years) through a systematic review of relevant studies. Materials and Methods: A systematic review was conducted on studies published in the last 10 years. Inclusion criteria were cross-sectional, case series, cohort, observational, and comparative studies in the English language. Exclusion criteria included studies published in non-English languages and articles older than 10 years. Articles were retrieved from various search engines and databases. Results: An initial search yielded 33,127 articles. After screening and refining based on inclusion and exclusion criteria, 15 articles were selected for detailed review. Of these, 10 studies (66.6%) reported a strong association between frozen shoulder and diabetes mellitus, while 1 study (6.6%) reported no significant association. Factors influencing the association included obesity, sedentary lifestyle, family history, physical inactivity, occupation, and trauma. The majority of studies highlighted a higher prevalence of frozen shoulder in women with Type 1 diabetes, particularly those aged around 45 years. Conclusion: This systematic review concludes that diabetes mellitus significantly affects the shoulder joint, leading to a higher prevalence of frozen shoulder among diabetic women of reproductive age. Contributing factors such as obesity, sedentariness, family history, and physical inactivity further exacerbate the condition. Keywords: Frozen shoulder, Diabetes mellitus, Type 1 diabetes, Women, Shoulder joint, Reproductive age, Occupation, Physical inactivity.